2017
DOI: 10.1177/0961203317731532
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing antiphospholipid antibodies following viral infection: a systematic review and meta-analysis

Abstract: Objective The objective of this paper is to conduct a systematic review and meta-analysis on the risk of developing elevated antiphospholipid (aPL) antibodies and related thromboembolic and/or pregnancy events following a viral infection. Method We searched Medline, EMBASE, Web of Science, PubMed ePubs, and Cochrane Central Register of Controlled Trials through June 2016. Independent observational studies of elevated aPL antibodies in patients with a viral infection compared with controls or patients with lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 78 publications
(74 reference statements)
5
88
0
7
Order By: Relevance
“…Furthermore, compared with patients without a cerebrovascular event, a significantly higher prevalence of antiphospholipid antibodies was observed in stroke patients. Previous studies have shown an increased risk of developing antiphospholipid antibodies in various viral infections (43). Our results indicate that clinicians should be aware of the increased risk and consider testing for antiphospholipid antibodies in patients with COVID-19 infection and clinical manifestations suggestive of APS.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, compared with patients without a cerebrovascular event, a significantly higher prevalence of antiphospholipid antibodies was observed in stroke patients. Previous studies have shown an increased risk of developing antiphospholipid antibodies in various viral infections (43). Our results indicate that clinicians should be aware of the increased risk and consider testing for antiphospholipid antibodies in patients with COVID-19 infection and clinical manifestations suggestive of APS.…”
Section: Discussionsupporting
confidence: 50%
“…This would provide important information for developing a protocol for perioperative hemostasis management for recipients in this part of the world, which might be different from other protocols used in overseas centers. However, the observed incidence of 25.2% for increased lupus anticoagulant in our study is in line with the increased incidence of lupus anticoagulant between 18 and 61% reported by other authors [27,28,29,30,31] for patients with hepatitis C, cirrhosis, and carcinoma. Notably, the main transplant indication in our patient population was HCV infection in 82% (41/50), even combined with HCC in 43% (18/41).…”
Section: Discussionsupporting
confidence: 93%
“…The theory that COVID-19 might stimulate the production of aPL has been put forward [93]. However, aPL are usually transient in the postinfection period and their clinical significance is ambiguous [94].…”
Section: -Clinical Phenotypementioning
confidence: 99%